PENGARUH IMPLEMENTASI SISTEM ERP TERHADAP KINERJA PERUSAHAAN - Donny Fernando (Teknik Informatika Fakultas Ilmu Komputer, 2020)
This study aims to enrich the literature on ERP systems and in this study we want to know how much influence the implementation of the ERP system in the company has on company performance. The model used in this study was adopted from the TAM (Technology Acceptance Model). In this study, a sample of 132 respondents was taken from 3 companies that have implemented the ERP system. Data were collected using questionnaires while data analysis used partial correlation, multiple, simple linear regression & multiple linear regression. Data were collected using google form media and analysis using Excel. Based on the results of the study it can be concluded that the quality of information and system quality has 76% influence on company performance and 24% is influenced by other variables.